Relationship between anxiety and static and dynamic balance disorder in subjects with cerebrovascular accident (stroke) diagnosis - Ferreira, Ana Paula Lemos; barbosa, Danillo (Manual Therapy, Posturology & Rehabilitation Journal, 2020)
Background: Sensory systems are responsible for maintaining balance, being vision, vestibular and somatosensory, and all these systems suffer changes in patients with stroke sequelae and studies bet that anxiety is likely to influence the inability of the subject to use these systems, enhancing the postural imbalance in stroke patients. Objective: To analyze the interference of anxiety on the static and dynamic balance of patients diagnosed with stroke. Methods: Fifteen patients with stroke, aged 40 to 80 years, were assessed using the Hospital Anxiety and Depression Scale, Timed Up and Go test for dynamic balance and the Berg Scale for static balance. Data were tabulated in Excel and analyzed using SPSS - Statistical Package for Social Science (version 20.0). Results: Significant values were found for the correlation between anxiety and balance, in which the results analyzed showed that the balance of patients with stroke can be negatively exacerbated due to the anxiety that affects them. Conclusion: It can be concluded from these results that anxiety can alter the balance of these patients and thus, it is shown the importance of a multidisciplinary treatment from the first moment to leverage the treatment.